Malaysia-Indonesia Cross Border Governance Policy in Accelerating Economic Development - Darmawan, Wawan Budi; Riyadi, Sayed Fauzan (Journal of Governance, 2024)
The regulation of the movement of people and goods across the border that separates Indonesia and Malaysia is of critical significance to the expeditious growth of each nation's economy. In light of this, the purpose of the study is to investigate the role that cross-border management policies have in fostering accelerated economic growth between Indonesia and Malaysia. The research makes use of a technique called a literature study, which entails collecting data from various articles, books, and papers that are associated with cross-border policy and governance between Indonesia and Malaysia. The findings of the study indicate that the policy and management of cross-border traffic between Indonesia and Malaysia still possess a very complicated character, and as a result, the two nations need to work together effectively. Its cross-border policy and governance are still deemed successful in that they have improved economic cooperation between the two nations, despite the fact that its execution faces various hurdles and problems. Larger and more synergistic efforts from both countries are required to be made in order to address the outstanding issues and improve the well-being of communities in border regions. As a result, the application of international law and strategies that span borders might provide an alternative to the utilization of policy models that are more efficient in the development of border regions.